From Dresden to the world: images of the German Hygiene Museum’s relations with Latin America, 1911-1933 - Pedro Felipe N. de Muñoz (História, Ciências, Saúde: Manguinhos)
Abstract As of the nineteenth century, the number of world fairs and hygiene exhibitions grew significantly. This phenomenon was linked to the experience of modernity and the emergence of bacteriology, when different cities were sanitized with the aim of combating urban diseases and epidemics. For the purpose of sanitary education and hygiene propaganda, many objects and pictures were displayed in hygiene exhibitions and museums, such as the International Hygiene Exhibition of 1911 and the German Hygiene Museum, both in Dresden. The goal of this article is to analyze a chapter of the international history of health through images that portray the connections between the German Hygiene Museum and Latin American countries between 1911 and 1933.